Creep behavior of the solid acid fuel cell material CsHSO4. (October 2017) - Ginder, Ryan S.; Pharr, George M.
Abstract: Solid acid materials have recently shown great promise as solid-state electrolytes in intermediate temperature fuel cells. However, little is currently known about their mechanical properties, some of which could severely limit their application. In this study, the steady state creep behavior of the prototypical solid acid, CsHSO4, is characterized. In its highly conductive superprotonic state (> 141 °C), the material creeps at very high rates, as high as 10 − 2  s − 1, at stresses in the application design range of only a few MPa. The steady state creep stress exponent n ≅ 3.6 and activation energy Q ≅ 1.02 eV = 98.8 kJ/mol are consistent with a dislocation-based creep mechanism. Graphical abstract: